2015
DOI: 10.1083/jcb.201412011
|View full text |Cite
|
Sign up to set email alerts
|

Both tails and the centromere targeting domain of CENP-A are required for centromere establishment

Abstract: New roles for the N-terminal histone tail and folded core of CENP-A are revealed by monitoring early steps in centromere establishment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
100
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 39 publications
13
100
1
1
Order By: Relevance
“…3A). Previous research showed that CENP-A Ser18 is phosphorylated in HeLa and U2OS cells (23,38), which we confirmed by mass spectrometry (data not shown). We then determined if the Cyclin E1/CDK2 kinase can phosphorylate GST-tagged full-length CENP-A in vitro .…”
Section: Resultssupporting
confidence: 88%
“…3A). Previous research showed that CENP-A Ser18 is phosphorylated in HeLa and U2OS cells (23,38), which we confirmed by mass spectrometry (data not shown). We then determined if the Cyclin E1/CDK2 kinase can phosphorylate GST-tagged full-length CENP-A in vitro .…”
Section: Resultssupporting
confidence: 88%
“…S1B,C), indicating that histones can be efficiently incorporated into chromatin at the LacO locus. Our results are in agreement with two recent reports that demonstrated that LacI-CENP-A is assembled into chromatin at or near LacO arrays using a similar system (Logsdon et al 2015;Tachiwana et al 2015). Therefore, using this LacO/I targeting system, the interaction between CENP-N and CENP-A chromatin can be analyzed.…”
Section: The Rg Loop Of Cenp-a Plays a Key Role In The Recruitment Ofsupporting
confidence: 81%
“…The CATD in the context of the rest of histone H3 (H3 CATD ) is sufficient to bind HJURP and direct its deposition to centromeres (Black et al 2004; Black et al 2007; Hu et al 2011). CENP-A equivalent substitutions in this mutant (H3 CATD-Q68S ) significantly enhances its ability to interact with HJURP (Logsdon et al 2015; Yu et al 2015). Nevertheless, the H3 mutant containing Ser-68 without the CATD remains unable to bind to HJURP, clearly reinforcing the idea that CATD is the primary determinant for CENP-A deposition to centromeres (Logsdon et al 2015; Yu et al 2015).…”
Section: Cenp-a Posttranslational Modifications and Deposition At Cenmentioning
confidence: 99%
“…1) (Black et al 2004). Sequences in the amino and carboxyl termini are not required for CENP-A deposition and appropriate targeting, but are involved in exerting CENP-A function in building the centromere (Fachinetti et al 2013; Foltz et al 2009; Logsdon et al 2015). Likewise, while the CATD is important for targeting CENP-A to the centromere, the two amino acid “bulge” Arg-80 and Gly-81 in the structure contributes to CCAN recruitment (Sekulic et al 2010; Tachiwana et al 2011).…”
Section: An Overview Of Cenp-a Structure and Posttranslational Modifimentioning
confidence: 99%
See 1 more Smart Citation